Effect of boronizing treatment on the oxidation resistance of Zr2(AlSi)4C5/SiC composite. (January 2020) - Lu, X.P.; Xiang, H.M.; Han, P.; Li, M.S.; Zhou, Y.C.
Highlights: The effect of SiC on the oxidation resistance of Zr2 [Al(Si)]4 C5 at 1000 °C is negative. A coating containing ZrB2 and SiC was prepared on the Zr2 [Al(Si)]4 C5 /30 vol.%SiC. Protective layers generated during oxidation of Zr2 [Al(Si)]4 C5 /30 vol.%SiC. The oxidation resistance of Zr2 [Al(Si)]4 C5 /30 vol.%SiC at 1000 °C was improved. The oxidation property of Zr2 [Al(Si)]4 C5 /30 vol.%SiC at 1800 °C was improved. Abstract: The oxidation behavior of Zr2 [Al(Si)]4 C5 /30 vol.%SiC composite(ZASC-30SC) at 900–1300 °C was investigated, and the effect of SiC additive on the oxidation resistance of Zr2 [Al(Si)]4 C5 at 1000 °C is negative. A boronizing coating containing ZrB2 and SiC was prepared through boronizing treatment. The effect of boronizing on the oxidation resistance of ZASC-30SC composite at 1000 °C and 1800 °C were explored respectively. At 1000 °C, the oxidation resistance was improved intensively as a result of a protective liquid B2 O3 containing scale formed during oxidation. Besides, the oxidation properties at 1800 °C of ZASC-30SC was improved obviously because of a protective SiO2 rich layer generated.